2016
DOI: 10.1371/journal.pone.0150938
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Drosophila for Investigating DUX4 and FRG1, Two Genes Associated with Facioscapulohumeral Muscular Dystrophy (FSHD)

Abstract: Facioscapulohumeral muscular dystrophy (FSHD) is typically an adult onset dominant myopathy. Epigenetic changes in the chromosome 4q35 region linked to both forms of FSHD lead to a relaxation of repression and increased somatic expression of DUX4-fl (DUX4-full length), the pathogenic alternative splicing isoform of the DUX4 gene. DUX4-fl encodes a transcription factor expressed in healthy testis and pluripotent stem cells; however, in FSHD, increased levels of DUX4-fl in myogenic cells lead to aberrant regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 99 publications
1
11
0
Order By: Relevance
“…Animal and cell model development has been a primary focus of the FSHD field and our laboratory since the DUX4 gene emerged more than a decade ago (35). During the last decade or so, several DUX4-expressing models have also been reported (6,9,(19)(20)(21)(22)(23)(24)(25)(26)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). One particularly important study that guided the design of our TIC-DUX4 mice was first reported as a scientific abstract in 2008 and published in 2014 (25,43).…”
Section: Discussionmentioning
confidence: 99%
“…Animal and cell model development has been a primary focus of the FSHD field and our laboratory since the DUX4 gene emerged more than a decade ago (35). During the last decade or so, several DUX4-expressing models have also been reported (6,9,(19)(20)(21)(22)(23)(24)(25)(26)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). One particularly important study that guided the design of our TIC-DUX4 mice was first reported as a scientific abstract in 2008 and published in 2014 (25,43).…”
Section: Discussionmentioning
confidence: 99%
“…Expression levels of CIC, ETV1, ETV4, ETV5, and WT1 were evaluated on both RNAseq platforms in comparison to other soft tissue tumors in each platform. The mRNA expression of known PEA3 family downstream target genes, including SPRY2, SPRY4, SPRED2, GPR20, DUSP6 GBX2, FGF8, POU5F1, MMP1/2/3/7/9, TWIST1, SNAI1/2, PTGS2, BAX, CCND2, ZEB1, PTK2, PLAU, ICAM1, VEGFA, NOTCH1, NOTCH4, and SPP1 was investigated from the whole transcriptome sequencing platform, while FRG1, PITX1, ZSCAN4, RFPL2, TRIM43, and LEUTX, were evaluated as DUX4 targets …”
Section: Methodsmentioning
confidence: 99%
“…The mRNA expression of known PEA3 family downstream target genes, including SPRY2, SPRY4, SPRED2, GPR20, DUSP6 GBX2, FGF8, POU5F1, MMP1/2/3/7/9, TWIST1, SNAI1/2, PTGS2, BAX, CCND2, ZEB1, PTK2, PLAU, ICAM1, VEGFA, NOTCH1, NOTCH4, and SPP1 10-19 was investigated from the whole transcriptome sequencing platform, while FRG1, PITX1, ZSCAN4, RFPL2, TRIM43, and LEUTX, were evaluated as DUX4 targets. [20][21][22][23] Cases studied by the whole transcriptome sequencing (n 5 10)…”
Section: Rna Sequencing Data Analysismentioning
confidence: 99%
“… 8 , 9 , 10 , 11 , 12 , 13 The identification of DUX4 as a target gene provided a platform to finally enable translational research on FSHD, by allowing the development of DUX4 -expressing animal models and DUX4 -targeted molecular therapies. 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21…”
Section: Introductionmentioning
confidence: 99%